ANALISIS PENGGUNAAN LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Kaysa Ananda; Shayla Naina Fikria; Muhammad Sofwan; Febby Ayuni Esya Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of Student Worksheets (LKPD) based on Problem Based Learning (PBL) in improving students' critical thinking skills in Natural and Social Science (IPAS) subjects at Elementary School. Critical thinking ability is one of the essential competencies in the 21st century, but in reality many elementary school learning activities are still passive and do not encourage students to think critically. The study used a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation studies. The research subjects were grade IV teachers and students at SDN 64/I Muara Bulian. The results showed that PBL-based LKPD was able to create meaningful learning experiences through contextual problem presentation, encouraging students to think analytically, ask questions, and formulate solutions independently. The most prominent aspects of critical thinking that developed were the ability to analyze, evaluate, and conclude. Thus, PBL-based LKPD proved effective as an IPAS learning medium that encourages critical thinking skills of Elementary School students.